1998
DOI: 10.1046/j.1365-2281.1998.00091.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic changes during prolonged coronary artery occlusion in man: comparison of standard and high‐frequency recordings

Abstract: Detection of acute myocardial ischaemia using electrocardiographic methods is generally based on assessment of the ST segments in the standard 12-lead electrocardiogram (ECG). Several studies have also shown changes in high-frequency QRS components during acute ischaemia. The purpose of the present study was to determine the changes in high-frequency QRS components during prolonged percutaneous transluminal coronary angioplasty (PTCA) and to compare these changes with ST-segment deviations in the standard 12-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
(9 reference statements)
0
12
0
Order By: Relevance
“…In humans, HF-QRS (150-250 Hz) has been recorded during PTCA (Pettersson et al, 1998(Pettersson et al, , 2000b. The results from these studies show that balloon-induced ischaemia leads to changes in HF-QRS RMS voltages in a majority of the patients.…”
Section: Hf-qrs In Acute Myocardial Ischaemiamentioning
confidence: 97%
“…In humans, HF-QRS (150-250 Hz) has been recorded during PTCA (Pettersson et al, 1998(Pettersson et al, , 2000b. The results from these studies show that balloon-induced ischaemia leads to changes in HF-QRS RMS voltages in a majority of the patients.…”
Section: Hf-qrs In Acute Myocardial Ischaemiamentioning
confidence: 97%
“…It has previously been shown that diminution of HF-QRS is a more sensitive detector of acute myocardial ischaemia than changes in the ST segment of standard ECG (Abboud et al, 1987;Pettersson et al, 1998Pettersson et al, ,2000a. It has previously been shown that diminution of HF-QRS is a more sensitive detector of acute myocardial ischaemia than changes in the ST segment of standard ECG (Abboud et al, 1987;Pettersson et al, 1998Pettersson et al, ,2000a.…”
Section: Rms-v1 (µV)mentioning
confidence: 99%
“…Different studies have reported high frequency energy changes (HFEC) during acute coronary occlusion. Abboud et al and Mor Avi et al [3,8] studied this phenomenon over human and animal models respectively; Petterson et al [4] could find HFEC even without ST deviations and obtained better sensitivity and specificity than the ST criteria. These studies of HFEC have used the 150-250Hz bandwidth, however, others research have included the bands of 80-300Hz [9], 20-30Hz, and 16-200 Hz [7], which shows that there is not a specific time-frequency region to evaluate HFEC.…”
Section: Introductionmentioning
confidence: 97%
“…Reversible ischemia was generally measured only during the repolarization process through ST segment deviation. Recent studies suggest that ischemic events can produce changes in highfrequency components of the QRS complex [3,4]. Because of its multi-resolution signal decomposition, wavelet analysis and specifically complex Morlet wavelet has been successfully used to characterize qualitatively patients prone to ventricular tachycardia (VT) [5,6] and short lasting events with the surface ECG before and after angioplasty [7].…”
mentioning
confidence: 99%